A way to reduce friction between ring and traveller of a ring spinning frame (Bangladesh Journal of Scientific and Industrial Research, 2013)
The paper presents a method, which applied to the ring of the ring spinning machine will improve its productivity. Through the system vibration is applied on the ring-traveller, which has effects on the centrifugal force of the traveller and helps the traveller to rotate around ring with intermittent contact. The effect of vibration on yarn tension as well as friction between the ring and the traveler and the corresponding raise in temperature of the ring during spinning are measured. An external facility is designed and incorporated in a miniature ring spinning frame to generate and apply vibration to the ring. The miniature ring spinning frame has the facility to vary twist and count of yarn and is modified to vary the spindle speed. Study shows that the ringtraveller friction is affected by the application of vibration. Results obtained with and without the applications of vibration are compared. It is found that yarn tension and friction between the ring and the traveller reduce significantly depending on the type of vibration. Therefore it can be concluded that application of vibration may be a way to reduce friction between the ring and the traveler and thus the mechanical process of twisting and winding can be done at higher speed for higher productivity which is a limiting factor of ring spinning system. Bangladesh J. Sci. Ind. Res. 47(4), 421-426, 2012 DOI: http://dx.doi.org/10.3329/bjsir.v47i4.14072